Detection of Oxygenated Hemoglobin in Human Blood Based on OptiCAL Biosensor Circuit - Wangmo et al., Sangay (International Journal of Advanced Science and Technology, 2020)
In this paper, an optical biosensor (OB) circuit was designed to investigate optical output power level of transmission to detect the small changes of refractive index (RI) in analyte which refers to concentration level of oxygenated hemoglobin in human blood.  OB circuit is built utilizing a waveguide of silicon-on-insulator (SOI). This OB circuit was designed using the INTERCONNECT module from LUMERICAL software. The effective index and group index of the waveguide (SOI) were 2.3 and 3.9 respectively. Overall circuit was implemented with transverse magnetic TM mode at the wavelength of 930nm. The detection of oxygenated hemoglobin is based on RI range from 1.334 to 1.340 in blood samples. From the results, can be observed that output power level was within 1mW and frequency measured range was between -0.2THz to 0.2THz. The accuracy sensitive of OB circuit was determined with full width at half maximum (FWHM) output power signal spectrum within the range of 0.07 – 0.08 GHz respectively. This OB circuit of detection sensitivity level is 880nm/RIU. Based on designed OB circuit, the detection of analyte is achieved with low power level.